REKOMENDASI PENJURUSAN DI SMU YSKI DENGAN ALGORITMA K-MEANS - Rosita Herawati, Rosita (PROXIES, 2012)
This research is tIllking about grouping senior high school students into 2 or 3 different groups. This research is located in SMA YSKI Semarang. The process of grouping students in this school is quite complicated. It is because of the diversity of the elements which is used to determine the student into groups. K-Means Algorithm is used to clustering students based on characteristics of each groups. As a system which able to recommend student into a group, then K-Means done in nested loops. This nested process done for catch any possibility if a student falls into 2 or 3 different groups. Every loops will grouping student into cluster in accordance with the characteristics of every groups.